Bracing NK cell based therapy to relegate pulmonary inflammation in COVID-19. Issue 7 (July 2021) - Jeyaraman, Madhan; Muthu, Sathish; Bapat, Asawari; Jain, Rashmi; Sushmitha, E.S.; Gulati, Arun; Channaiah Anudeep, Talagavadi; Dilip, Shirodkar Jaswandi; Jha, Niraj Kumar; Kumar, Dhruv; Kesari, Kavindra Kumar; Ojha, Shreesh; et al.
Abstract: The contagiosity of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has startled mankind and has brought our lives to a standstill. The treatment focused mainly on repurposed immunomodulatory and antiviral agents along with the availability of a few vaccines for prophylaxis to vanquish COVID-19. This seemingly mandates a deeper understanding of the disease pathogenesis. This necessitates a plausible extrapolation of cell-based therapy to COVID-19 and is regarded equivalently significant. Recently, correlative pieces of clinical evidence reported a robust decline in lymphocyte count in severe COVID-19 patients that suggest dysregulated immune responses as a key element contributing to the pathophysiological alterations. The large granular lymphocytes also known as natural killer (NK) cells play a heterogeneous role in biological functioning wherein their frontline action defends the body against a wide array of infections and tumors. They prominently play a critical role in viral clearance and executing immuno-modulatory activities. Accumulated clinical evidence demonstrate a decrease in the number of NK cells in circulation with or without phenotypical exhaustion. These plausibly contribute to the progression of pulmonary inflammation in COVID-19 pneumonia and result in acute lung injury. In this review, we have outlined the present understanding of the immunological response of NK cells in COVID-19 infection. We have also discussed the possible use of these powerful biological cells as a therapeutic agent in view of preventing immunological harms of SARS-CoV-2 and the current challenges in advocating NK cell therapy for the same. Abstract : SARS-CoV-2; COVID-19; Natural killer cells; Cytokines; Pulmonary inflammation.